100 knits : Interweave's ultimate pattern collection (Interweave, an imprint of F+W Media Inc., 2018)
"Page after page of knitting patterns are at your fingertips with 100 Knits, giving you a nearly endless supply of projects you'll be excited to cast on. From hats to shawls, cardigans to tanks and tees, explore a massive variety of Interweave's most popular knitting patterns all in one source! In this ultimate knitting pattern collection you'll discover: Expansive collection of Interweave's most coveted knitted sweater patterns together for the first time. From shawls, scarves and cowls, to socks and hats, you'll be covered head to toe in our trendiest accessory patterns. Endless inspiration for your next knit with over 500 pages of patterns." --